Production and Quality Pennisetum purpureum at Shading Condition and Nitrogen Fertilizer Dosage - Mangiring, Windu; Kurniawati, Nurleni; Priyadi, Priyadi (Jurnal Penelitian Pertanian Terapan, 2017)
This experiment aims to determine 1) The effect of  shading and nitrogen fertilizer to production   of Pennisetum purpureum ; and 2) The effect of  shading and nitrogen fertilizer  to quality of Pennisetum purpureum,experiment performed in January until May 2016at fieldSTIPER Dharma Wacana Metro.The experiment was investigated in random block design with three replication. The first factor is consisted of two treatment of shading level, i.e (0%) without shading  and (50%)  paranet shade. The second factor consisted of three treatment of nitrogen fertilizer dosage, i.e 50 kgha-1 nitrogen fertilizer, 100 kgha-1nitrogen fertillizer and 200 kgha-1 nitrogen fertilizer. The results showed that effect paranet shade 50% in fact evidently  decrease the production of Pennisetum purpureum 60 %. Quality of Pennisetum purpuremlike  nitrate content, crude protein content  and crude fiber contenton 50%paranet shade 0,2%-0,11%;7,8%-10,8%; and 29,13%-30,00%. In shade condition, a dose of 50 kgha-1not significant production of elephant grass forage, elephant grass forage production response to increasing doses of N (50-200 kgha-1)is more significant than whitout shade. Key words : Pennisetum purpureum,elephant grass, paranet shade, nitrogen